2006
DOI: 10.3928/1081-597x-20060201-17
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Cornea for up to Four Years After Photorefractive Keratectomy for Myopia

Abstract: PURPOSE:To analyze the long-term corneal topographic changes 4 years after myopic photorefractive keratectomy (PRK). METHODS:This study comprised 15 patients (30 eyes) who had PRK surgery with a scanning-spot excimer laser (Chiron Technolas 217C; Bausch & Lomb, Dornach, Germany) and were followed up to 4 years after surgery. The eyes were subdivided into three groups according to the preoperative spherical equivalent refraction. Corneal topographic maps were obtained for all eyes with a Placido disc topographe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…[33][34][35] When the central portion of the anterior cornea has mechanically stable curvature in the very long-term postoperative period, as reported previously, 23,24,33,34 it contributes to the stability of corneal optical performance.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[33][34][35] When the central portion of the anterior cornea has mechanically stable curvature in the very long-term postoperative period, as reported previously, 23,24,33,34 it contributes to the stability of corneal optical performance.…”
Section: Discussionmentioning
confidence: 94%
“…The ablation design and parameters, 36-43 epithelial healing, and biomechanics of the corneal tissue [33][34][35] are the main sources of HOA induction, which can influence the optical result after PRK. The increase in spherical aberration in the optical ablation zone after simple myopic ablations could be due to causes other Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Interpolation to the same spaced referenced cornea grid was necessary for this purpose, as discussed in previous works. [7][8][9] A central zone with radius (r) of 1.00 mm from the corneal apex and a peripheral annular zone with 3.00 Յ r Յ 4.00 mm from the apex were delineated for detailed regional analysis of anterior corneal topography changes during follow-up. The choice of the regions' width was based on results of previous studies.…”
Section: Topographic Analysismentioning
confidence: 99%
“…In previous studies, 8,9 we described the topographic response of the cornea to PRK for myopia and demonstrated how the anterior cornea undergoes minimal changes of the central optical portion up to 6 years after surgery. In the present study, we describe the long-term variation of the whole anterior corneal morphology over an 8-year follow-up after PRK for the correction of myopia or myopic astigmatism.…”
mentioning
confidence: 97%
See 1 more Smart Citation